Survival outcomes in carcinoma cervix with contemporary radiation therapy: an insight - Srivastava, Himanshu; Kalyanpur, Tejas; Singh Pruthi, Harnoor; Negi, Preety (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Concurrent chemoradiation therapy (CCRT) followed by brachytherapy is the standard of care treatment for locally advanced cervical cancer (stage IB3-IVA disease). The present study aimed to evaluate the success achieved by CCRT followed by computed tomography (CT)-based brachytherapy in patients with locally advanced carcinoma cervix in a tertiary care center. Methods: This was a prospectively conducted retrospective observational study of patients with cervical carcinoma, treated at Capitol Hospital, Jalandhar, Punjab, from January 2018 to December 2021. Data were captured from the electronic medical records of the hospital. Overall survival (OS) and disease-free survival (DFS) were calculated using the Kaplan-Meier curve. The survival analysis was assessed by the patient’s age, tumor stage, histology, and overall treatment duration. Results: This study included 129 patients treated with CRT followed by CT-based brachytherapy. The median follow-up was 30 months (range 8-67 months). The 2-year OS and DFS were 83.5% and 80.2%, respectively. On univariate analysis, the factors associated with better survival were histology, and treatment duration, although not statistically significant. Conclusions: Our treatment results with definitive CCRT followed by CT-based brachytherapy for locally advanced cervical carcinoma are comparable to the published literature. The prognostic factors such as tumor histology and treatment duration (<65 days) influenced patient survival, with squamous cell carcinoma, and completion of the treatment within 65 days resulted in better survival rates.